Stop caretaking the borderline or narcissist : how to end the drama and get on with life - Fjelstad, Margalis, 1945- (Rowman & Littlefield Publishers, 2013)
People with borderline or narcissistic personality disorders have a serious mental illness that primarily affects their intimate, personal, and family relationships. Often they appear to be normally functioning at work and in public interactions, and Narcissists may even be highly effective, in the short term, in some work or social situations. However, in intimate relationships, they can be emotional, aggressive, demeaning, illogical, paranoid, accusing, and controlling in the extreme. Their ability to function normally or pleasantly can suddenly change in an instant, like flipping a switch. These negative behaviors do not happen once in a while, they happen almost continuously in their intimate relationships and most often, and especially with their caretaker family member. Here, the author describes how people get into a caretaker role with a borderline or narcissist, and how they can get out. Caretakers give up their sense of self to become who and what the borderline or narcissist needs them to be. This compromises the caretaker's self-esteem, distorts their thinking processes, and locks them into a victim-persecutor-rescuer pattern with the borderline or narcissist. The book looks at the underlying rules and expectations in these relationships and shows caretakers how to move themselves out of these rigid interactions and into a healthier, more productive, and positive lifestyle, with or without the borderline/narcissistic partner or family member. It describes how to get out of destructive interactions with the borderline or narcissist and how to take new, more effective actions to focus on personal wants, needs, and life goals while allowing the borderline or narcissist to take care of themselves. It presents a realistic, yet compassionate, attitude toward the self-destructive nature of these relationships, and gives real life examples of how individuals have let go of their caretaker behaviors with creative and effective solutions.